2020 28th European Signal Processing Conference (EUSIPCO) 2021
DOI: 10.23919/eusipco47968.2020.9287525
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Doppler Signal Representation for Drone Classification by Deep Learning

Abstract: There are numerous formats which represent the micro-Doppler signature. Our goal is to determine which one is the most adapted to classify small UAV (Unmanned Aerial Vehicules) with Deep Learning. To achieve this goal, we compare drone classification results with the different micro-Doppler signatures for a given neural network. This comparison has been performed on data obtained during a radar measurement campaign. We evaluate the classification performance in function of different use conditions we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…where k is the number of elements in each subset. Next, the first-order difference function is applied to (17) in range m = 1, 2, . .…”
Section: F Npaqm Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where k is the number of elements in each subset. Next, the first-order difference function is applied to (17) in range m = 1, 2, . .…”
Section: F Npaqm Methodsmentioning
confidence: 99%
“…However, ever smaller drone sizes, low altitude operation, low flying speed, and the urban environment highly reduce the radar detection accuracy. Considering these limitations, the Authors in [17] investigate the micro-Doppler signatures induced by the micro-motion of small drones. While effectiveness against drones performing autonomous tasks is a valuable asset, high power active radar beam, needed for long-range detection, usually limits its use to licensed users.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the reasons why HERM line analysis is not very well explored. Recently, Gérard et al [28] compared the efficiency of using different micro-Doppler representations, such as the the HERM line spectrum, the cepstrum, CVD, the spectrogram to classify five different drones using a CNN. The same integration time (0.3 s) was used for all these representations and it was found that using the HERM line spectrum performed the best and was the most resistant against noise.…”
Section: Long-window Herm Line-based Methodsmentioning
confidence: 99%
“…Drone classification using micro-Doppler is typically done by training classifiers using different micro-Doppler representation like the cepstrum, cadence velocity diagram and the short windowed STFT spectrogram. Recently, it was shown that using the HERM line spectrum to classify drones was superior to other micro-Doppler representations such as the cepstrum, CVD, and the short-window spectrogram given the same integration time[28]. However, using a smaller window of data of 0.03 s rather than 0.3 s, the classification accuracy dropped from 98% to 93%.…”
mentioning
confidence: 99%